The Effect of Company Size, Profitability, Solvency and Audit Opinion on Audit Delay - Roza Mulyadi; Shinta Octavianti; Indra Sulistiana (Journal of Applied Business, Taxation and Economics Research, 2022)
This study aims to prove the factors that affect audit delay. The factors tested in this study are company size, profitability, solvency and audit opinion. This study uses quantitative methods and uses secondary data types. Secondary data collection is carried out on food and beverage companies listed on the Indonesia Stock Exchange in 2017-2021 which are accessed through www.idx.co.id in the form of an Annual Report. Obtained a sample of 80 Food & Beverage companies listed on the Indonesia Stock Exchange in 2017-2021 using the purposive sampling method. The statistical method used in this study is multiple linear regression at a significance level of 5% with the test instrument of SPSS version 25 computer program. The results of this study indicate that profitability and solvency have a significant negative effect on audit delay, firm size and audit opinion have no effect on audit delay and firm size, profitability, solvency and audit opinion simultaneously affect audit delay